Radiofrequency identification technology can standardize and document blood collections and transfusions. - Sandler SG; Langeberg A; Debandi L; Gibble J; Wilson C; Feldman CL (Transfusion, 2007)
BACKGROUND: We evaluated the potential for radiofrequency (RF) transponder microchips to standardize and document key steps in the blood collection and transfusion process. STUDY DESIGN AND METHODS: Using the blood center's standard operating procedures for blood collections, we programmed a laptop computer and 10 multiwrite 256-byte RF microchips to prompt operators to enter data for key steps in blood collection. Before collections, RF microchips were attached to blood collection sets at the blood center. In parallel with actual collections, we added data to the microchips with the computer and a hand-held scanner-programmer. After labeling, we shipped the RF microchip-tagged blood units to the hospital where unit-related data (whole blood number, ABO and Rh, expiration date, special laboratory test results) were uploaded from the RF microchip to the transfusion service's information system. The microchip was subsequently used as a cross-match label for blood unit-recipient matching. RESULTS: Data were successfully uploaded to the RF microchip at key steps during blood collections. Software programs in the laptop computer and hand-held scanner-programmer successfully prompted operators to enter key data. At any stage in a blood collection, authorized operators were able to review electronic records of prior steps using the laptop computer or by scanning the microchip attached to the blood bag. Unit-related data were successfully transferred to the hospital transfusion service through the RF microchip. These data were successfully incorporated in the RF microchip cross-match label, which was used to confirm recipient-blood unit matching at the bedside. CONCLUSION: RF microchips can collect key data during blood collections, facilitate information transfer from the blood center to the hospital, and confirm recipient-blood unit matching at the bedside before transfusions.